Loss of Dnah5 Downregulates Dync1h1 Expression, Causing Cortical Development Disorders and Congenital Hydrocephalus - Koichiro Sakamoto; Masakazu Miyajima; Madoka Nakajima; Ikuko Ogino; Kou Horikoshi; Ryo Miyahara; Kaito Kawamura; Kostadin Karagiozov; Chihiro Kamohara; Eri Nakamura; Nobuhiro Tada; Akihide Kondo (Cells)
Dnah5 is associated with primary ciliary dyskinesia in humans. Dnah5-knockout (Dnah5−/− mice develop acute hydrocephalus shortly after birth owing to impaired ciliary motility and cerebrospinal fluid (CSF) stagnation. In contrast to chronic adult-onset hydrocephalus observed in other models, this rapid ventricular enlargement indicates additional factors beyond CSF stagnation. Herein, we investigated the contributors to rapid ventricular enlargement in congenital hydrocephalus. Dnah5−/− mice were generated using CRISPR/Cas9. The expression of dynein, N-cadherin, and nestin in the cerebral cortex was assessed using microarrays and immunostaining. Real-time PCR and Western blotting were performed for gene and protein quantification, respectively. All Dnah5−/− mice developed hydrocephalus, confirmed by electron microscopy, indicating the absence of axonemal outer dynein arms. Ventricular enlargement occurred rapidly, with a 25% reduction in the number of mature neurons in the motor cortex. Dync1h1 expression was decreased, while cytoplasmic dynein levels were 56.3% lower. Levels of nestin and N-cadherin in the lateral ventricular walls decreased by 31.7% and 33.3%, respectively. Reduced cytoplasmic dynein disrupts neurogenesis and axonal growth and reduces neuron cortical density. Hydrocephalus in Dnah5−/− mice may result from cortical maldevelopment due to cytoplasmic dynein deficiency, further exacerbating ventricular enlargement due to CSF stagnation caused by impaired motile ciliary function.